2015
DOI: 10.1039/c5py00674k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of water soluble polyrotaxanes by end-capping polypseudo-rotaxanes of γ-CDs with PHEMA-PPO-PEO-PPO-PHEMA using ATRP of MPC

Abstract: A twice ATRP protocol is developed for the preparation of water soluble single-chain stranded polyrotaxanes (PRs) by end-capping polypseudorotaxanes (PPRs) formed from γ-CDs with PHEMA-PPO-PEO-PPO-PHEMA using oligomers of 10 MPC as bulky stopper. It is shown that those threaded γ-CDs simultaneously reside on PHEMA and PEG segments to give access to both loose-and over-fit structured PR-based multiblock copolymers.Single-chain stranded cyclodextrin (CD)-based polyrotaxanes 15 65

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…This is due to the restricting and shielding effects from the inner cavity of γ-CDs against the vibration of the corresponding chemical bond [ 22 ]. This confirmed that the PMPC segments were successfully attached to two ends of the pentablock polymer to convert γ-CD/PMA-PPO-PEO-PPO-PMA PPRs into the PR-based multiblock copolymers [ 14 , 23 ].…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…This is due to the restricting and shielding effects from the inner cavity of γ-CDs against the vibration of the corresponding chemical bond [ 22 ]. This confirmed that the PMPC segments were successfully attached to two ends of the pentablock polymer to convert γ-CD/PMA-PPO-PEO-PPO-PMA PPRs into the PR-based multiblock copolymers [ 14 , 23 ].…”
Section: Resultsmentioning
confidence: 68%
“…In two recent articles [ 13 14 ], we reported that attaching PHEMA to two ends of PPO-PEO-PPO via ATRP of HEMA could change its self-assembly process with γ-CDs. Wherein, the γ-CDs were threaded onto and moved over the PHEMA segments to give access to unmatched γ-CD/PHEMA-PPO-PEO-PPO-PHEMA PPRs showing a mixed loose-fit (with PEO) and over-fit (with PHEMA) architecture, instead of the PEO-bent double-chain-stranded tight-fit ones like those of γ-CD/BrPEPBr PPRs [ 15 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several CD-based polyrotaxanes known with homo- and block-copolymer axes, mostly based on poly(ethylene oxide), poly(propylene oxide) or their copolymers [ 15 21 ], since these polymers can form sufficiently stable complexes with CDs. The application potential of these polyrotaxanes was already investigated in the fields of biomedicine, as drug [ 22 ] or gene [ 23 ] delivery vehicles, or in materials sciences, as slide ring gels [ 6 ].…”
Section: Introductionmentioning
confidence: 99%